Neurological Recovery after Surgical Intervention in Patients with Traumatic Spinal Cord Injury (SCI). A single centre experience - Satar , Abdul; Khan, Muhammad Zahid; Khan Kabir, Samir; Khan , Arif (Indus Journal of Bioscience Research, 2024)
Objective:  To determine the frequency of neurological recovery in patients with traumatic spinal cord injuries (SCI) following surgical intervention at the Department of Orthopedic & Spine Surgery, Hayatabad Medical Complex, Peshawar.Methodology:  This was a retrospective, cross-sectional study conducted from June 2016 to June 2024. A total of 354 patients with traumatic SCI who underwent surgical intervention were included. Data were collected from hospital records and analyzed using the ASIA (American Spinal Injury Association) grading system for neurological outcomes. Statistical analysis was performed using SPSS, with a significance level of p < 0.05.Results:  Out of 354 patients, 270 (76.3%) were male, and 84 (23.7%) were female, with a mean age of 31.81 years (SD ± 13.31). Falls from height were the leading cause of injury (63.6%). Neurological recovery, defined as an improvement of at least one ASIA grade, was observed in 268 (75.7%) patients. Among patients with ASIA A, 17.53% showed improvement, while 86.66% of ASIA B, 83.04% of ASIA C, and 43.7% of ASIA D patients experienced neurological improvement post-surgery.Conclusion:  The study findings underscore the significant potential for neurological recovery following surgical intervention in SCI patients, particularly in those with incomplete injuries. The results highlight the importance of early and tailored surgical management for optimal recovery.